Sports journalism : a history of glory, fame, and technology - Washburn, Patrick Scott; Lamb, Chris, 1958- (University of Nebraska Press, 2020)
"Sports Journalism tells the full story of American sports journalism and the notable changes in technology that have dramatically changed how Americans consumed it"--